Effects of population on food security, health care and education expenditure in China and India - Nordin, Nurhaiza (2016)
This study examines the impact of population on food security, health care and education expenditure between China and India. The increase in population especially in size and growth increases the challenges to countries like China and India in ensuring sufficient food, healthy life and education level. The objective of this study is first to examine the effects of population and food dimension on food security; second to investigate the impact of population on health care expenditure and the third objective is to investigate the impact of young population on education expenditure in China and India. The Autoregressive Distributed Lags (ARDL) developed by Pesaran et al. (2001) was employed for the analysis and data cover period from 1970-2012. The empirical result showed that population has an impact on food security and at the same time, food dimension played an important role to ensure sufficient food. The increase in population has an impact on food security, which means that when food demands increase, food security will decrease. However, with the three food dimension; food availability, food accessibility and food utilization, food are secured and sufficient to support the demand. The impact of population and food dimension on food security is higher in China in the long-run rather than in India but lower in short-run. The impacts on population and population ages structure on health care expenditure have serious issues. Health is important to ensure a healthy life, thus a positive relationship exists between population and health care expenditure. The impact of population size on health care expenditure is higher in China than India, while for population growth, it is vice versa means higher in India than in China. Looking into the population ages structure, the relationship between population ages 0-14 years, 15-64 years and 65 years and above has a positive impact on health care expenditure both in long-run and short-run estimation. Population ages 0- 14 years, result estimates that the impact of population on health care expenditure are higher in China, but for population ages 15-64 years and 65 years and above are higher in India than in China both in long-run and short run estimation. The third objective is the relationship between the young populations with the education expenditure. The result confirms that, increase in young population had positive and significant impact on education expenditure. In the long-run, the impact of young population on education expenditure were higher in India rather than China. However, in the short-run China had a higher impact than India. The findings confirm that population have an impact on food security, health care and education expenditure in China and India. For the recommendation, firstly, ensure the food security with the increase in population. Being aware that food security measures dietary energy supply adequacy where people can easily access to food at all time. Then, food dimension itself, plays a crucial role in ensuring a sufficient and adequate food. Lastly, health care and education both are crucial and much needed in developed and developing countries as healthy and educated community builds great nation. A policy aimed in encouraging health care and education where it requires creating a fitter and more productive society to support China’s and India’s economic development and growth. The people of today shapes the world of tomorrow.